The Disappearing Act: Heritage Making in Charlotte Riddell’s Novels - Colella, Silvana (English Literature, 2019)
This article examines the strategies of heritage making in Riddell’s City novels, popular in the 19th century, but little known today. Drawing on late Victorian debates about the preservation of the past and its material remains, the article focuses on the relationship between fictional and non-fictional elements, in Riddell’s urban realism, which frequently pivots on heritage concerns. The main argument is twofold: 1) heritage discourse provides an apt frame for the self-validation of the author’s daring narrative choices; 2) Riddell’s understanding of heritage changes as her vision of capitalism darkens, culminating in a vocal denunciation of the destructive forces at work in the very idea of progress. Her novels generate heritage value in the very gesture of recording the many disappearing acts mournfully witnessed by the narrator.